PENGARUH WAKTU PERENDAMAN TiO2 DALAM LARUTAN EKSTRAK ANTOSIANIN BUNGA ROSELLA PADA KINERJA DYE SENSITIZED SOLAR CELL (DSSC) - Rafika Andari; Dona Abrini (Komunikasi Fisika Indonesia, 2018)
The use of solar panels is still quite expensive in the making, for it needs to be developed solar panels are cheap based DSSC (Dye Sensitized Solar Cell). The use of DSSC is very good developed in Indonesia which is famous for its biological richness. This study used rosella flowers as photosensitizer obtained from the extraction process in the form of maceration for 24 hours. The components used to construct a DSSC outline can be divided into four parts, namely substrate, dye, semiconductor titanium dioxide (TiO2), and electrolyte. In this research the Ti O2 layer was immersed in a solution of rosella flower extract with different time variations, ie 1 hour, 2 hours, and 3 hours. Light sources used are sunlight and 150 watt halogen lamps. It was found that at 3 hours of immersion using the sunlight source was the best result of maximally current (Imax) 0.3 mA, maximum voltage (V) 582,4 mV and its efficiency 0,258%. The results obtained were lower when the DSSC was given a halogen light source, i.e. Maximum current (Imax) 0.08 mA, maximal voltage (Vmax) 125,6 mV and its efficiency 0,167%. The greater the intensity of the light illumination the greater the output power of the DSSC.The use of solar panels is still quite expensive in the making,  for it needs to be developed solar panels are cheap based DSSC (Dye Sensitized Solar Cell). The use of DSSC is very good developed in Indonesia which is famous for its biological richness. This study used rosella flowers as photosensitizer obtained from the extraction process in the form of maceration for 24 hours. The components used to construct a DSSC outline can be divided into four parts, namely substrate, dye, semiconductor titanium dioxide (TiO2), and electrolyte. In this research the TiO2 layer was immersed in a solution of rosella flower extract with different time variations, ie 1 hour, 2 hours, and 3 hours. Light sources used are sunlight and 150 watt halogen lamps. It was found that at 3 hours of immersion using the sunlight source was the best result of maximally current (Imax) 0.3 mA, maximum voltage (Vmax) 582,4 mV and its efficiency 0,258%. The results obtained were lower when the DSSC was given a halogen light source, i.e. Maximum current (Imax) 0.08 mA, maximal voltage (Vmax) 125,6 mV and its efficiency 0,167%. The greater the intensity of the light illumination the greater the output power of the DSSC.